2011
DOI: 10.1016/j.ijgo.2011.09.007
|View full text |Cite
|
Sign up to set email alerts
|

User fees and maternity services in Ethiopia

Abstract: Utilization of maternal health services is extremely low in Ethiopia and, although there is a government decree against charging for maternity service, 65% of health centers do charge for some aspects of maternal care. As health facilities are not reimbursed by the government for the costs of maternity services, this loss of revenue may account for the more and better services offered in facilities that continue to charge user fees. User fees are not the only factor that determines utilization in settings wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 8 publications
(8 reference statements)
6
94
0
Order By: Relevance
“…Until recently, the fee waiver system was characterized by ineffectiveness in specifically targeting the poor, incompleteness of coverage of services, and lack of proper documentation [18][19][20]. Although some reports suggest betterment of services with user fees, there is an apparent "crowding out effect" of fee increment by public health facilities, especially on the poor segments of the society in the absence of protective mechanisms [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, the fee waiver system was characterized by ineffectiveness in specifically targeting the poor, incompleteness of coverage of services, and lack of proper documentation [18][19][20]. Although some reports suggest betterment of services with user fees, there is an apparent "crowding out effect" of fee increment by public health facilities, especially on the poor segments of the society in the absence of protective mechanisms [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the reviewed sources showed that the Ethiopian society is highly exposed to increasing user fees for health care services and adverse effects of out-of-pocket expenditures for health care. Risk protection systems are at their level of infancy in Ethiopia [16,[18][19][20]34].…”
Section: Discussionmentioning
confidence: 99%
“…Only 2.8% Table 4: Attitude of health care providers towards delivery kits stock-outs. oped to increase the use of obstetric services and improve the quality of emergency care [12]. It was in this context that each government was asked to mobilize all necessary resources to reduce deaths related to the third delay [13,14].…”
Section: Attitudes and Practices Of Personnel When Drug Stock-outs Inmentioning
confidence: 99%
“…One of the main areas of intervention is to reduce the large catastrophic expenses incurred by families during childbirth [14]. In many countries, free care has been a means to reduce mortality by addressing financial barriers to access to quality childbirth [12,[15][16][17][18]. In Cameroon, after the intervention of the PASSAGE project, the strategy of pre-positioning of kits had been effective since 2011.…”
Section: Attitudes and Practices Of Personnel When Drug Stock-outs Inmentioning
confidence: 99%
“…This has been especially detrimental for vulnerable groups with limited access to financial resources (i.e., adolescents, elderly, women engaged in the informal economy; Parkhurst et al, 2005;WHO, 2010a). Childbirth services (including caesarean sections) have been found unaffordable and in some instances involve catastrophic costs across a range of LMICs (Honda, Randaoharison, & Matsui, 2011;Pearson, Gandhi, Admasu, & Keyes, 2011;Titaley, Hunter, Dibley, & Heywood, 2010). This is described further in the commentary on China (Fang, 2014).…”
Section: Introductionmentioning
confidence: 99%